2006
DOI: 10.1111/j.1365-2141.2006.06297.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in patients with Wiskott–Aldrich syndrome following stem cell transplantation: an analysis of 57 patients in Japan

Abstract: SummaryA total of 57 patients with Wiskott-Aldrich syndrome (WAS) were studied after undergoing stem cell transplantation (SCT) in Japan between January 1985 and December 2004. Eleven patients received transplants from human leucocyte antigen (HLA)-matched related donors, 10 from HLA-mismatched related donors, 21 from unrelated bone marrow donors, and 15 from unrelated cord blood donors. Nine of the 57 patients rejected the initial graft. The overall 5-year survival rate was 73AE7% and the 5-year failure-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
1
69
0
Order By: Relevance
“…[83][84][85][86] On the other hand, transplantation using the bone marrow of a mismatched related donor results in a decreased survival rate. [83][84][85][86] In addition, this type of transplantation is associated with an elevated risk of developing life-threatening EBV ϩ lymphoproliferative syndrome, infections, autoimmunity, and graft-versushost disease. 84 When a suitable related donor is not available, bone marrow or cord blood transplantation from a matched unrelated donor is a valid therapeutic option, leading to a 71% to 81% survival rate.…”
Section: Current Therapeutic Approaches and Perspectives For Gene Thementioning
confidence: 99%
See 2 more Smart Citations
“…[83][84][85][86] On the other hand, transplantation using the bone marrow of a mismatched related donor results in a decreased survival rate. [83][84][85][86] In addition, this type of transplantation is associated with an elevated risk of developing life-threatening EBV ϩ lymphoproliferative syndrome, infections, autoimmunity, and graft-versushost disease. 84 When a suitable related donor is not available, bone marrow or cord blood transplantation from a matched unrelated donor is a valid therapeutic option, leading to a 71% to 81% survival rate.…”
Section: Current Therapeutic Approaches and Perspectives For Gene Thementioning
confidence: 99%
“…23,84,85 A better outcome for matched unrelated donor and mismatched related donor HSCT in patients younger than 5 and 2 years of age, respectively, has been reported, suggesting that transplantations should be performed early in life. 79,84,85 Successful HSCT with establishment of full chimerism leads to restoration of immune and hemostatic functions. In patients with stable mixed chimerism in both myeloid and lymphoid compartments, clinical conditions usually improve.…”
Section: Current Therapeutic Approaches and Perspectives For Gene Thementioning
confidence: 99%
See 1 more Smart Citation
“…7,16 This broad range of manifestations is explained by WASp function, which is tightly associated with the actin cytoskeleton formation, especially in actin polymerization. 3,11,17,18 A successful therapy for WAS can be achieved by allogenic bone marrow (BM) stem cell transplantation 19,20 or unrelated umbilical cord blood transplantation when a compatible donor is not available, 21 but the risk of graft vs host disease and rejection cannot be excluded in any case. [19][20][21] To overcome these limitations, gene therapy using autologous haematopoietic stem cells (HSCs) is a real alternative for treating WAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed in Japan on 57 WAS patients treated with HSCT showed that 5 year-old patients suffering from classic WAS, at the time of transplantation had increased susceptibility to infection and hemorrhage diathesis had shown already poor prognosis. Therefore, timely diagnosis and starting treatment of WAS seems to be very important (9). Interestingly, in our study all the symptoms and infections vanished after treatment with monthly IVIG and prophylactic antibiotics, and treatment with HSCT was not needed.…”
Section: Discussionmentioning
confidence: 71%